Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 22

Answer

x = 1 y = 4

Work Step by Step

5x + 4y -2 = -6 + 7y -3x 3x + 4x = y + 3 simplify to the second equation 3x + 4x = y +3 7x = y + 3 minus 3 to both sides 7x - 3 = y + 3 - 3 7x - 3 = y substitude y = 7x - 3 to the first equation 5x + 4 ( 7x - 3 ) -2 =- 6 + 7 ( 7x - 3 ) - 3x use the distributive property 5x + 28 x - 12 - 2 =- 6 + 49x - 21 - 3x simplify 33x -14 = -27 + 46x minus 46x to both sides 33x - 14 - 46x = -27 + 46x - 46x - 13x - 14 = -27 - 13x - 14 + 14 = -27 + 14 add 14 to both sides -13x =-13 $\frac{-13x}{-13}$ = $\frac{-13}{-13}$ divide both sides by -13 x = 1 y =7x - 3 substitude x = 1 y = $7\times1$ - 3 y = 7 - 3 y = 4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.